DINAMIKA CRYPTOCURRENCY DAN MISI EKONOMI ISLAM - Umam, Ahmada Khoirul; Wardhana, Onny Herlambang Putra; Hany, Ira Humaira (UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Advances in technology that exist today, have brought people to a lot of reforms in various aspects; fashion, automotive, communication and payment systems. developments that exist in the payment system, not only mobilizing people to be able to transact more effective and efficient. Furthermore, it is able to lead humans to a monetary system reformation such as the existence of various cryptocurrencies. However, this progress must be able to be monitored, because we know that everything’s like two sides of a coin. Islam as a kaffah system has a responsibility to anticipate the various possibilities that exist. Through literature review in this paper, the author tries to provide various important matters in the dynamics of cryptocurrencies, and how the Islamic economy’s role in order to supervise, make a contribution to the existing dynamics.